Strategies for Implementing Project-Based Learning to Enhance Student Collaboration Skills in Religious Education at the Senior High School Level with a Managerial Approach - Kamilah, Fitrotul; Mansur, Umar (Al-Qalam Institue, 2025)
This study explores the use of Project-Based Learning (PBL) in religious education at the senior high school level, aiming to enhance students' collaboration skills. By focusing on real-world projects, PBL fosters teamwork, critical thinking, and the application of religious principles in everyday life. A school known for its diverse student body and innovative teaching approaches, the study uses a qualitative case study design. Data was gathered through semi-structured interviews with teachers, students, and administrators, along with direct classroom observations. The results indicate that PBL significantly improved students' collaboration abilities, including communication, responsibility-sharing, and conflict resolution. However, challenges such as time constraints and students’ difficulty in linking abstract religious concepts to practical projects were noted. Teachers used strategies like rotating leadership roles, reflection discussions, and managing group dynamics to facilitate learning. Despite the success, the study highlights the need for teacher training and curriculum adjustments to overcome the limitations of time and address the unique challenges of applying PBL in religious education. Overall, PBL proves to be an effective approach to increasing student engagement and understanding, though its implementation methods require refinement to suit religious content.